“Taxonomic certification versus the scientific method”: a rebuttal of Rogers (2012) - Stribling, James; Sweeney, Bernard; Morse, John; Corkum, Gail; Lester, Gary; Miller, Scott; Mitchell, Richard; Poulton, Barry; Strachan, Stephanie; Wetzel, Mark (Zootaxa, 2012)
We read with great interest the correspondence article entitled “Taxonomic certification versus the scientific method” (Rogers 2012), and, as members of the Taxonomic Certification Committee of the Society for Freshwater Science (formerly, the North American Benthological Society [NABS, 1975–2011]) (SFS-TCC 2012), we agreed to respond in a constructive fashion with factual information to correct and provide perspective for a few errors, unfounded and confused assumptions, and misperceptions it presents. The nature and structure of the article and its title requires that our response be segregated into two main parts. First, we briefly describe the philosophy, purpose, and objectives of the Taxonomic Certification Program (TCP [http://www.sfstcp.com/]) as developed and administered by the SFS, including correcting inaccurate statements or false assumptions. Second, we will address the issues Rogers has with terminology used in a paper he cites (Stribling et al. 2003 [not 2002 as cited by Rogers]). The former issue is, by far, most important—primarily because it has the potential of adversely affecting a program that has already had a large positive impact on the quality of biological monitoring in the USA and Canada by recognizing laboratory staff with demonstrated ability to perform taxonomic identifications of benthic macroinvertebrate samples. The terminology issue is trivial, but because the comments are made in print, we correct them in print by rebutting Rogers’ perception that we were in error.